SAT0216 Juxtaarticular and general osteoporosis in rheumatoid arthritis – results of dxa-densitometry. (1st June 2001) - Welcker, M; Gottwalt, J; Wienands, K; Franck, H
Abstract : Background: Juxtaarticular osteoporosis is an early sign of inflammation in conventional radigraphy in Rheumatoid arthritis. Objectives: It should be shown weather juxtaarticular osteoporosis can be analysed by dual x-ray adsorption (DXA) and if there is a correlation to general bone loss in inflammatory joint disease. Methods: 20 patients with Rheumatoid arthritis and 10 patients with Fibromyalgia were analysed by DXA (Hologic 2000). Regions of interest (ROIs) were the spine, the hip, the forearm and juxtaarticular subregions of the fingers. Results: Patients with Rheumatoid arthritis showed decreased bone densities of the spine, the hip, the forearm and the juxtaarticular joint region of the fingers. This was the case in late and early stages (Larsen 0–1) of the disease. The relative loss of juxtaarticular bone density was in these cases comparable to the relative loss of bone density of the spine and the hip. Conclusion: DXA revealed loss of juxtaarticular bone density in patients suffering from Rheumatoid arthritis. This could be a method for objective estimation of juxtaarticular osteoporosis in the early course of Rheumatoid arthritis. Infection related rheumatic diseases